Mekanisme-Mekanisme Justifikasi Kebenaran Religius - Subianto Bunyamin, Antonius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
Religious justifications might have happened as a result of religion’s too much self confidence, if not of self absolutization that ended up in uncertainty. Perhaps religions need to be aware of Francis Bacon’s warning that “if a man will begin with certainties, he shall end in doubts, but if he will be content to begin with doubts, he shall end in certainties.” Religions need to do what Kant already called as pure critique when saying that reason’s autocritique has its own limitations. Religions need to carry on autocriticism and autoreflection so as not to fall into self absolutization. Instead of justifying itself, religion has to struggle to prove itself meaningful for individuals and communities, for the institution itself and other organizations. In lieu of justifying God, it has to justify humankind and to create the world ‘humanum’. KeyWords:*kebenaran religius, *rasionalisasi, *pembenaran diri religius, *agama, *mekanisme, *justifikasi, *kritik terhadap agama, *autokritik.